Clinical significance of circulating dendritic cells in patients with systemic lupus erythematosus. Issue 3 (2004) - Robak, E.; Smolewski, P.; Woźniacka, A.; Sysa-Jędrzejowska, A.; Robak, T.
Abstract : DENDRITIC cells are a complex group of mainly bone-marrow-derived leukocytes that play a role in autoimmune diseases. The total number of circulating dendritic cells (tDC), and their plasmacytoid dendritic cell (pDC) and myeloid dendritic cell (mDC1 and mDC2) subpopulations were assessed using flow cytometry. The number of tDC and their subsets were significantly lower in systemic lupus erythematosus patients than in the control group. The count of tDC and their subsets correlated with the number of T cells. The number of tDC and pDC subpopulation were lower in the patients with lymphopenia and leucopoenia than in the patients without these symptoms. Our data suggest that fluctuations in blood dendritic cell count in systemic lupus erythematosus patients are much more significant in pDC than in mDC, what may be caused by their migration to the sites of inflammation including skin lesions. Positive correlation between dendritic cell number and TCD4 +, TCD8 + and CD19 + B cells, testify of their interactions and influence on SLE pathogenesis. The association between dendritic cell number and clinical features seems to be less clear.